2010
DOI: 10.1371/journal.pone.0009303
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of DNA Binding 3 Limits Development of Murine Slam-Associated Adaptor Protein-Dependent “Innate” γδ T cells

Abstract: BackgroundId3 is a dominant antagonist of E protein transcription factor activity that is induced by signals emanating from the αβ and γδ T cell receptor (TCR). Mice lacking Id3 were previously shown to have subtle defects in positive and negative selection of TCRαβ+ T lymphocytes. More recently, Id3 −/− mice on a C57BL/6 background were shown to have a dramatic expansion of γδ T cells.Methodology/Principal FindingsHere we report that mice lacking Id3 have reduced thymocyte numbers but increased production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 64 publications
8
96
3
Order By: Relevance
“…Thus, a very small number of highly related sequences constitute .75% of the expressed Vd6.4 chains in Thy-1 dull gd T cells from DBA/2 mice (16). The same sequences were also found in the Vd6.3 chains expressed by Thy-1 dull gd T cells and by NK1.1 + gd T cells in the B6 background, albeit at lower frequencies (13,16,23). These sequences are characterized by a germline Dd2-Jd1 junction that leaves intact both gene segments and imposes a unique reading frame of the Dd2 and by a V-Dd2 junction with little trimming of the ends of the segments and limited N-nucleotide addition.…”
supporting
confidence: 61%
“…Thus, a very small number of highly related sequences constitute .75% of the expressed Vd6.4 chains in Thy-1 dull gd T cells from DBA/2 mice (16). The same sequences were also found in the Vd6.3 chains expressed by Thy-1 dull gd T cells and by NK1.1 + gd T cells in the B6 background, albeit at lower frequencies (13,16,23). These sequences are characterized by a germline Dd2-Jd1 junction that leaves intact both gene segments and imposes a unique reading frame of the Dd2 and by a V-Dd2 junction with little trimming of the ends of the segments and limited N-nucleotide addition.…”
supporting
confidence: 61%
“…2B). In contrast to recent studies, which reported an expansion of NKT cells expressing a γ/δ TCR in mice with mutations within proximal TCR signaling molecules or a lack of the transcription factor Id3 [55][56][57][58][59][60][61], we did not observe an accumulation of this rare NKT cell subset in slp-76 ace/ace mice (data not shown). Thus, besides NK cells [53] the slp-76-mutation specifically affects α/β-TCR + iNKT cells.…”
Section: Slpcontrasting
confidence: 99%
“…In fact, Id3-null mice have increased generation of "innate-like" gd cells expressing TCR Vg1.1 Vd6.3 with limited junctional diversity. This gd T cell subset shares phenotypic and functional characteristics with ab NKT cells (27) and is repressed by Id3 (30,31). In line with a role of P2X7 activity in the ERK-Egr-Id3 signaling pathway, p2rx7 2/2 mice displayed increased peripheral representation of this cell subset, suggesting a role of extracellular ATP in modulating gd NKT cell development.…”
Section: Stimulation P2rx7mentioning
confidence: 67%
“…Although the ERK-Egr-Id3 signaling axis plays a role in gd lineage development, mice lacking Id3 display elevated numbers of gd T cells (26,30,31). In fact, Id3-null mice have increased generation of "innate-like" gd cells expressing TCR Vg1.1 Vd6.3 with limited junctional diversity.…”
Section: Stimulation P2rx7mentioning
confidence: 99%